The Anatomical Studies of the Kidneys of Rhode Island Red (RIR) and White Leghorn (WLH) Chicken During Their Postnatal Stages of Growth and Development - Islam, Kh.N.; Khan, M.Z.I.; Siddiqui, M.S.I.; Islam, M.R.; Lucky, N.S.; Hossain, M.K.; Adhikary, G.N. (International Journal of Poultry Science, 2004)
The anatomical studies of the kidneys of Rhode Island Red (RIR) and White Leghorn (WLH) chicken during their postnatal stages of growth and development were investigated in the present study. The chicken were grouped into day old, day 30, day 90, day 180 and day 360.The gross structures of the kidney (weight, relative weight, length, breadth and thickness) during their growth period were estimated by using the measuring balance and scale. The histological structures of the kidney (the nephrons, the number of glumerulae and the presence of collagen and elastic fibers within the kidney) were also studied by light microscope using hematoxylin and eosin stain, Van Gieson and Verhoeff`s stain. The gross structures were significantly higher in the RIR than the WLH chicken whereas the histological structure (number of glomerulae) were higher in WLH than RIR chicken. From these data it may be suggested that these differences did not depend on the developmental stages of growth and development but depend on the genetic variation of the chicken.